Sodium, Glucose and Dysregulated Glucagon Secretion: The Potential of Sodium Glucose Transporters - Armour, Sarah L.; Frueh, Alexander; Knudsen, Jakob G. (Frontiers in Pharmacology, 2022)
Diabetes is defined by hyperglycaemia due to progressive insulin resistance and compromised insulin release. In parallel, alpha cells develop dysregulation of glucagon secretion. Diabetic patients have insufficient glucagon secretion during hypoglycaemia and a lack of inhibition of glucagon secretion at higher blood glucose levels resulting in postprandial hyperglucagonaemia, which contributes to the development of hyperglycaemia. Sodium-glucose co-transporter 2 (SGLT2) inhibitors are an efficient pharmacologic approach for the treatment of hyperglycaemia in type 2 diabetes. While SGLT2 inhibitors aim at increasing glycosuria to decrease blood glucose levels, these inhibitors also increase circulating glucagon concentrations. Here, we review recent advances in our understanding of how SGLTs are involved in the regulation of glucagon secretion. Sodium plays an important role for alpha cell function, and a tight regulation of intracellular sodium levels is important for maintaining plasma membrane potential and intracellular pH. This involves the sodium-potassium pump, sodium-proton exchangers and SGLTs. While the expression of SGLT2 in alpha cells remains controversial, SGLT1 seems to play a central role for alpha cell function. Under hyperglycaemic conditions, SGLT1 mediated accumulation of sodium results in alpha cell dysregulation due to altered cellular acidification and ATP production. Taken together, this suggests that SGLT1 could be a promising, yet highly underappreciated drug target to restore alpha cell function and improve treatment of both type 1 and 2 diabetes